2012
DOI: 10.1007/s00709-012-0474-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunoanalysis of dehydrins in Araucaria angustifolia embryos

Abstract: The aim of this study was to describe the dehydrin content of mature Araucaria angustifolia embryos, a species of endangered and economically important conifers, native to southern Brazil, northeastern Argentina, and eastern Paraguay. The A. angustifolia seeds have been categorized as recalcitrant. Dehydrins were studied by western blot analysis and in situ immunolocalization microscopy using antibodies raised against the K segment, a highly conserved lysine-rich 15-amino acid sequence extensively used to reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The localization and functional versatility of dehydrins has been widely studied with respect to plant tolerance against multiple abiotic stresses. Dehydrins are ubiquitously localized in different parts of cells, such as cytoplasm, nucleus, chloroplasts, vacuole, endoplasmic reticulum, mitochondria, cytoplasm and cell membranes [ 9 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. Some dehydrins are also found to be localized in several parts of cells under abiotic stresses.…”
Section: Localizations and Functions Of Dehydrinsmentioning
confidence: 99%
“…The localization and functional versatility of dehydrins has been widely studied with respect to plant tolerance against multiple abiotic stresses. Dehydrins are ubiquitously localized in different parts of cells, such as cytoplasm, nucleus, chloroplasts, vacuole, endoplasmic reticulum, mitochondria, cytoplasm and cell membranes [ 9 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. Some dehydrins are also found to be localized in several parts of cells under abiotic stresses.…”
Section: Localizations and Functions Of Dehydrinsmentioning
confidence: 99%
“…Starch and lipids are among compounds stored in greater quantities in embryos of mature seeds of A. angustifolia (Farias-Soares et al, 2013), but the FTIR spectroscopy results demonstrated that proteinaceous compounds are, quantitatively as important as lipids, and phenolic constituents are also present in large quantities. Regardless of condition, storage resulted in changes in metabolic profile compared to freshly harvested samples.…”
Section: Discussionmentioning
confidence: 95%
“…In recent years, many studies have been conducted to examine seed development and/or somatic/zygotic embryogenesis of A. angustifolia (Balbuena et al, 2009;Agapito-Tenfen, Steiner, Guerra, & Nodari, 2011;Balbuena et al, 2011;Farias-Soares, Burrieza, Steiner, Maldonado, & Guerra, 2013;Rogge-Renner et al, 2013;Shibata, Coelho, & Steiner, 2013;Farias-Soares et al, 2014;Jo, Santos, Bueno, Barbosa, & Floh, 2014;Fraga, Vieira, Puttkammer, Oliveira, & Guerra, 2015;Steiner et al, 2015), and even though knowledge of the botanical varieties of this species has been reported since 1966 by Reitz and Klein (1966), little attention has been devoted to the characterization of these varieties. In this study, the results show a great diversity of the characteristics studied, and knowledge of varieties may contribute to their maintenance and regeneration.…”
Section: Resultsmentioning
confidence: 99%